PEMETAAN TINGKAT KOROSIFITAS DI DAERAH DKI JAKARTA[Corrosion Mapping of Corrosivity Level in DKI Jakarta] - Nasoetion, Ronald (Jurnal Metalurgi, 2012)
CORROSION MAPPING OF CORROSIVITY LEVEL IN DKI JAKARTA. Global warming and contamination of enviromental will increase degree of corrosivity due to industrial growing, motor vehicles consuming and urban populating. On the other hand, degree of corrosivity due to those conditions is still unmeasurable. The aim of this research is measuring degree of athmospheric corrosivity of several locations in DKI Jakarta at various area such as : marine, industrial, urban and rural. This study concern to various factors that affect to metal corrosion rate in atmospheric, such as : climated factors, polutant, waste gas and ion chloride from sea water. Corrosion rate of various metal for structures or process tools of industries is measured periodically by weight loss method. The result of this research shown that the high corrosivity is at marine area with the average of corrosion rate around 20.02 mdd. The average corrosion rate at industries environment, cities and urbans are around 11.04 mdd, 4.79 mdd and 5.35 mdd, respectively. From this research, degree of corrosivity could be mapped at several locations in DKI Jakarta.